2016
DOI: 10.1242/dev.135400
|View full text |Cite
|
Sign up to set email alerts
|

Generation of intestinal surface: an absorbing tale

Abstract: The vertebrate small intestine requires an enormous surface area to effectively absorb nutrients from food. Morphological adaptations required to establish this extensive surface include generation of an extremely long tube and convolution of the absorptive surface of the tube into villi and microvilli. In this Review, we discuss recent findings regarding the morphogenetic and molecular processes required for intestinal tube elongation and surface convolution, examine shared and unique aspects of these process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 109 publications
4
99
0
Order By: Relevance
“…However, tools for genetic manipulation in a tissue specific manner are more limited in the chick. Additionally, there are significant differences between avian and mammalian gut development that may limit cross-species comparisons [18]. The embryonic mouse model develops in a similar time frame to the avian embryo (19–21 days), and as an advantage, has an extensive set of tools for tissue specific genetic manipulation.…”
Section: Models Of the Developing Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…However, tools for genetic manipulation in a tissue specific manner are more limited in the chick. Additionally, there are significant differences between avian and mammalian gut development that may limit cross-species comparisons [18]. The embryonic mouse model develops in a similar time frame to the avian embryo (19–21 days), and as an advantage, has an extensive set of tools for tissue specific genetic manipulation.…”
Section: Models Of the Developing Intestinementioning
confidence: 99%
“…Villus morphogenesis is a process where the flat pseudostratified intestine begins to remodel and give rise to villus structures, which consist of finger-like epithelial protrusions into the intestinal lumen with an underlying mesenchymal core [18,23]. Villus formation massively expands the intestinal epithelial surface area, allowing for sufficient nutrient absorption to sustain life.…”
Section: Villus Formationmentioning
confidence: 99%
“…(Figure 3A) On the other hand, due to a thicker epithelium, it has been put forward that pattern formation in the mouse gut requires localized biochemical signals in addition to mechanical forces. [4244]…”
Section: Computational Modeling Of Intestinal Organoid Systemsmentioning
confidence: 99%
“…Many prior studies have explored the feasibility of growing the different cells of the intestinal tract and loading these cells on biomaterials in the physical shape of intestine for in vivo implantation [17,33,34]. The concept is to utilize autologous tissue to obviate the need for immunosuppression.…”
Section: Biongineeringmentioning
confidence: 99%
“…The concept is to utilize autologous tissue to obviate the need for immunosuppression. A recently published review article specific to TESI highlights our current understanding of the morphologic and molecular fundamentals of TESI [33]. One group that has previously shown that human and murine TESI possess histologic features of small bowel has demonstrated the functional capacity of their TESI constructs [17].…”
Section: Biongineeringmentioning
confidence: 99%